Insight into the Mechanisms of Carbapenem Resistance in Klebsiella pneumoniae: A Study on IS26 Integrons, Beta-Lactamases, Porin Modifications, and Plasmidome Analysis - Chien-Hao Tseng; Yao-Ting Huang; Yan-Chiao Mao; Chung-Hsu Lai; Ting-Kuang Yeh; Chung-Mei Ho; Po-Yu Liu (MDPI AG, 2023)
The emergence of carbapenem-resistant Klebsiella pneumoniae poses a significant threat to public health. In this study, we aimed to investigate the distribution and genetic diversity of plasmids carrying beta-lactamase resistance determinants in a collection of carbapenem-resistant K. pneumoniae blood isolates. Blood isolates of carbapenem-resistant K. pneumoniae bacteremia were collected and identified. Whole-genome sequencing, assembly and analysis were performed for the prediction of antimicrobial resistance determinants. Plasmidome analysis was also performed. Our plasmidome analysis revealed two major plasmid groups, IncFII/IncR and IncC, as key players in the dissemination of carbapenem resistance among carbapenem-resistant K. pneumoniae. Notably, plasmids within the same group exhibited conservation of encapsulated genes, suggesting that these plasmid groups may serve as conservative carriers of carbapenem-resistant determinants. Additionally, we investigated the evolution and expansion of IS26 integrons in carbapenem-resistant K. pneumoniae isolates using long-read sequencing. Our findings revealed the evolution and expansion of IS26 structure, which may have contributed to the development of carbapenem resistance in these strains. Our findings indicate that IncC group plasmids are associated with the endemic occurrence of carbapenem-resistant K. pneumoniae, highlighting the need for targeted interventions to control its spread. Although our study focuses on the endemic presence of carbapenem-resistant K. pneumoniae, it is important to note that carbapenem-resistant K. pneumoniae is indeed a global problem, with cases reported in multiple regions worldwide. Further research is necessary to better understand the factors driving the worldwide dissemination of carbapenem-resistant K. pneumoniae and to develop effective strategies for its prevention and control.